2022
DOI: 10.1126/sciadv.abm7103
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature skyrmion lattice in a layered magnet (Fe 0.5 Co 0.5 ) 5 GeTe 2

Abstract: Novel magnetic ground states have been stabilized in two-dimensional (2D) magnets such as skyrmions, with the potential next-generation information technology. Here, we report the experimental observation of a Néel-type skyrmion lattice at room temperature in a single-phase, layered 2D magnet, specifically a 50% Co–doped Fe 5 GeTe 2 (FCGT) system. The thickness-dependent magnetic domain size follows Kittel’s law. The static spin textures and spin dynamics in FCGT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 68 publications
2
93
0
Order By: Relevance
“…[1] Since the discovery of intrinsic 2D magnetism in van der Waals (vdW) materials, [17,18] layered magnets have become attractive platforms for spintronics. Magnetic skyrmions have been successfully created in Cr 2 Ge 2 Te 6 , Fe 3 GeTe 2 , and Fe 5 GeTe 2 , [13,[19][20][21][22][23] whereas the room-temperature THE were rarely reported. Recent studies reported the THE-like bumps and dips in Fe 3 GeTe 2 , [24,25] while it needs the magnetic field to be applied along a different crystallographic direction from the one for skyrmion creation.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Since the discovery of intrinsic 2D magnetism in van der Waals (vdW) materials, [17,18] layered magnets have become attractive platforms for spintronics. Magnetic skyrmions have been successfully created in Cr 2 Ge 2 Te 6 , Fe 3 GeTe 2 , and Fe 5 GeTe 2 , [13,[19][20][21][22][23] whereas the room-temperature THE were rarely reported. Recent studies reported the THE-like bumps and dips in Fe 3 GeTe 2 , [24,25] while it needs the magnetic field to be applied along a different crystallographic direction from the one for skyrmion creation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, room‐temperature skyrmion lattice has recently been observed in Co‐doped Fe 5 GeTe 2 . [ 84 ] The doping of Co atoms changes the crystal structure to the P 6 3 mc space group, resulting in the DMI and Néel‐type skyrmions. Another recent study reported a record high T c of 478 K in Ni‐doped Fe 5 GeTe 2 .…”
Section: Resultsmentioning
confidence: 99%
“…[ 171 ] In addition, its broken inversion symmetry gives rise to Néel‐type skyrmions. [ 172 ] Considering the successful large‐scale epitaxial growth of Fe 3 GeTe 2 and Fe 5 GeTe 2 , [ 177,178 ] wafer‐sized (Fe 0.5 Co 0.5 ) 5− x GeTe 2 may be achieved using a similar approach because of the similarity in their in‐plane lattice parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Zhang et al [ 171 ] reported a 2D polar ferromagnet, (Fe 0.5 Co 0.5 ) 5− x GeTe 2 , with a Curie temperature of ≈350 K. Notably, Néel‐type skyrmions were observed in this material at room temperature. [ 172 ] The findings on room‐temperature skyrmions in 2D magnets pave the way for skyrmion‐based 2D IMDs. Although related research remains in its infancy, the great potential of magnetic skyrmions opens an interesting perspective for future exploration of emerging memories based on 2D magnets.…”
Section: Imds: Mechanisms Architectures and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation